A kind of acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material and preparation method thereof

The magnesium-rich nickel slag geological polymer refractory gelling materials are stimulated by acid, and the dihydrogen phosphate exciter is used to solve the problems of medium- and high-temperature performance and compressive strength of nickel ferroslag treatment in the prior art, achieving efficient and environmentally friendly gelling materials preparation.

CN116573866BActive Publication Date: 2025-04-29UNIV OF SHANGHAI FOR SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310285336.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-04-29
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

In the prior art, when treating nickel-iron slag, the high iron content in fly ash affects the high temperature performance of geological polymers, and the porous structure limits the compressive strength.

Method used

Acid-energized magnesium-rich nickel slag geological polymer refractory gelling materials are used to stimulate dihydrogen phosphate as an exciter to form a gelling phase with high temperature bonding properties, improving the thermal stability and refraction resistance of the material.

Benefits of technology

It realizes gelling materials with high compressive strength while having a certain degree of fire resistance, simplifies the process, reduces costs, and improves the comprehensive utilization level of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116573866B_ABST
    Figure CN116573866B_ABST
Patent Text Reader

Abstract

The present invention relates to an acid-activated magnesium-rich nickel slag geopolymer refractory gelling material and a preparation method thereof, wherein the refractory gelling material comprises a solid raw material and a liquid raw material, wherein the solid raw material comprises magnesium-rich nickel slag and dihydrogen phosphate acidic activator, wherein the solid raw material phosphorus-aluminum molar ratio is (0.2-1.5):1, and the liquid raw material comprises water, wherein the liquid raw material and the solid raw material mass ratio is (0.2-0.4):1; the method comprises preparing slurry, preparing clean slurry and molding and curing, specifically: mechanically mixing the solid raw material magnesium-rich nickel slag and dihydrogen phosphate to obtain slurry; adding liquid raw materials to the slurry to mix to obtain clean slurry; pouring the clean slurry into a mold to form, and then curing to obtain a geopolymer refractory gelling material. Compared with the prior art, the present invention utilizes acid-activated solid waste to prepare a refractory gelling material, which has simple process, green energy-saving, and low cost, and can be used as a refractory prefabricated part with a certain compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization of industrial solid wastes, and relates to an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material and a preparation method thereof. Background Art

[0002] With the rapid development of the stainless steel industry, China's annual output of nickel-iron slag has exceeded 30 million tons, becoming the fourth largest typical metallurgical waste after blast furnace slag, steel slag and red mud, but only 8% is used for Portland cement production, port and road construction. At present, my country's treatment of nickel-iron slag is mostly on-site disposal or landfill. However, nickel-iron slag contains heavy metal ions, which may penetrate or leach after long-term accumulation, thereby polluting land and water resources.

[0003] In the process of alkali-activated geopolymers, the -OH radicals in the alkaline activator destroy the aluminosilicate precursor, causing the Si-O bonds and Al-O bonds in the structure to break. Alkaline cations such as Na + , K + After balancing the negative charges in the structure, it repolymerizes to form a gel such as [NASH] or [CASH], achieving electrical charge balance.

[0004] Patent CN114276066A discloses a magnesium-nickel-rich slag geopolymer porous material and a preparation method, comprising: 500-900 parts of magnesium-nickel-rich slag, 100-500 parts of fly ash, 100-400 parts of activator, 200-400 parts of water, 1-100 parts of foaming agent, and 1-30 parts of foam stabilizer; the activator comprises Na2SiO3, NaOH and phosphoric acid. When the activator is NaOH, the proportion of the activator in the total raw materials is the proportion of pure NaOH; when the activator comprises Na2SiO3 and NaOH, the proportion of the activator in the total raw materials is the proportion of pure Na2SiO3 and NaOH added together; when the activator comprises phosphoric acid, the proportion of the activator in the total raw materials is the proportion of pure phosphoric acid. However, experiments have shown that excessive iron content in fly ash will have a negative impact on the high-temperature performance of geopolymers; the excessive amount of foaming agent in this patent will also cause the foamed geopolymer to form through holes, thereby increasing the thermal conductivity of the material, while the porous structure greatly limits its compressive strength.

[0005] Patent CN113880506A discloses a phosphoric acid-activated magnesium-nickel slag geopolymer cementitious material and a preparation method thereof, including a cementitious material composed of magnesium-nickel slag and fly ash, mainly composed of the following components: by weight, 50-90 parts of magnesium-nickel slag, 50-10 parts of fly ash, 10-20 parts of phosphoric acid, and 20-40 parts of water. However, silicon dioxide (SiO2) in magnesium-nickel slag mainly exists in the form of quartz and magnesium iron crystals, so the raw material activity is poor; when the magnesium-nickel slag is activated by phosphoric acid, the dissolved aluminum and silicon elements are small, resulting in less gel phase generated; at the same time, the main research point of the patent is the compressive mechanical properties of the cementitious material, and does not involve the high temperature resistance of the material. Summary of the invention

[0006] The purpose of the present invention is to provide an acid-activated magnesium-nickel-rich slag geopolymer refractory cementitious material and a preparation method in order to overcome at least one defect of the above-mentioned prior art. The present invention utilizes acid-activated solid waste to prepare cementitious materials, which embodies the advantages of simple process, green energy saving and low cost; the material has a certain refractoriness and also has a high compressive strength.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material, which comprises a solid raw material and a liquid raw material, wherein the solid raw material comprises magnesium-nickel-rich slag and dihydrogen phosphate acidic activator powder, the solid raw material (a system composed of magnesium-nickel-rich slag and dihydrogen phosphate) has a phosphorus-aluminum molar ratio of (0.2-1.5):1, the liquid raw material comprises water, and the mass ratio of the liquid raw material to the solid raw material is (0.2-0.4):1.

[0009] my country uses laterite nickel ore as raw material, and the discharged nickel-iron slag is not only rich in silicon and aluminum, but also rich in magnesium. Through geological polymerization reaction, silicon, aluminum, magnesium and other elements can be converted into refractory gelled phase. At the same time, the main crystal structure of magnesium-rich nickel slag is forsterite, quartz and other mineral phases with high strength, high melting point and good chemical stability, so it can be used to prepare high temperature resistant materials.

[0010] Unlike alkaline excitation, the Al-OP bond formed by aluminosilicate in an acidic environment does not require the addition of cations to achieve charge balance like alkaline excitation. The difference between the two mechanisms makes acid-excited geopolymers have better refractoriness. Therefore, the method of preparing nickel-iron slag into an environmentally friendly gelled refractory cementitious material can not only replace cement, but also solve the environmental problems caused by improper treatment of nickel-iron slag.

[0011] Furthermore, the magnesium-nickel-rich slag includes 20-50 parts of silicon dioxide (SiO2), 20-50 parts of magnesium oxide (MgO), 10-30 parts of iron oxide (Fe2O3), 5-10 parts of aluminum oxide (Al2O3), 0-5 parts of calcium oxide (CaO), 0-1 part of manganese monoxide (MnO), 0-1 part of potassium oxide (K2O), 0-1 part of vanadium pentoxide (V2O5), 0-1 part of nickel oxide (NiO), 0-2 parts of titanium dioxide (TiO2) and 0-1 part of sulfur trioxide (SO3).

[0012] Furthermore, the dihydrogen phosphate includes aluminum dihydrogen phosphate (Al(H2PO4)3), magnesium dihydrogen phosphate (Mg(H2PO4)2) or calcium dihydrogen phosphate (Ca(H2PO4)2).

[0013] Under high temperature conditions, the activator undergoes a dehydration reaction as shown in the following formula (a) to generate a refractory phase aluminum metaphosphate (Al(PO3)3). Therefore, the present invention has more excellent thermal stability and refractoriness.

[0014] Al(H2PO4)3→Al(PO3)3+3H2O (a)

[0015] One of the technical solutions of the present invention is to provide a method for preparing an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material, the method comprising the following steps:

[0016] S1. Preparing slurry: placing solid raw materials, magnesium-nickel-rich slag and dihydrogen phosphate, in a stirrer and mechanically mixing them at a uniform speed to obtain slurry;

[0017] S2. Prepare clean slurry: add liquid raw materials into the slurry, continue to mix evenly, and obtain clean slurry;

[0018] S3. Forming and curing: pouring the pure slurry into an uncovered steel mold for forming, followed by curing to obtain a green solid waste-based geopolymer refractory gelling material with a certain strength.

[0019] Furthermore, the magnesium-nickel-rich slag is powder-refined before mixing in step S1, and the specific steps are: drying the magnesium-nickel-rich slag in an oven until the mass no longer changes, ball-milling the magnesium-nickel-rich slag in a ball mill after cooling to room temperature, and then sieving.

[0020] Furthermore, the drying temperature is 40-80°C.

[0021] Furthermore, the particle size of the magnesium-nickel-rich slag is 60-120 meshes.

[0022] Furthermore, the mixing speed in steps S1 and S2 is 150-400 rpm, the mixing time in step S1 is 1-5 min, and the mixing time in step S2 is 5-10 min.

[0023] Furthermore, the curing step in step S3 is specifically as follows: after sealing the mold poured with the clean slurry, the mold is placed in a curing box for constant temperature curing, and after demoulding, the test block is placed indoors for curing, and then placed outdoors for curing to obtain the geopolymer refractory gelling material.

[0024] Furthermore, the constant temperature curing time is 12-36 hours, the temperature is 35-50°C, the indoor curing time is 3-5 days, the temperature is 10-30°C, and the outdoor curing time is 7-28 days, the temperature is 5-20°C.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) The activator of the present invention is different from conventional acidic activators. It uses dihydrogen phosphate with high-temperature bonding properties. The gel phase comes not only from the geological polymerization process, but also from the activator itself, so that the present invention has more excellent thermal stability and refractoriness;

[0027] (2) The present invention adopts a water-binder ratio of (0.2-0.4):1, and the prepared test block shows good mechanical properties. The refractory cementitious material is prepared using solid waste, and the efficient utilization of magnesium-nickel-rich slag is achieved, which reflects the commercial value of solid waste, improves the comprehensive utilization level of solid waste, helps the construction of ecological civilization, provides strong support for the high-quality development of the economy and society, and creates the possibility of replacing aluminate cement (refractory cement);

[0028] (3) The present invention uses geopolymerization technology to obtain a refractory cementitious material at room temperature. Compared with the "two grindings and one burning" of traditional aluminate cement (refractory cement) and the preparation of refractory bricks by sintering nickel-iron slag, the experimental process of the present invention is simpler, green and energy-saving, low-cost, and has good commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The X-ray diffraction (XRD) diagram of the acid-activated magnesium-nickel-rich slag geopolymer refractory gelled material in Example 1 of the present invention;

[0030] Figure 2 The XRD diagram of the acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material in Example 2 of the present invention;

[0031] Figure 3 The XRD diagram of the acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material in Example 3 of the present invention;

[0032] Figure 4 The XRD diagram of the acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material in Example 4 of the present invention;

[0033] Figure 5 The XRD diagram of the acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material in Example 5 of the present invention;

[0034] Figure 6 This is a scanning electron microscope (SEM) image of the acid-activated magnesium-nickel-rich slag geopolymer refractory gelled material in Example 2 of the present invention. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0036] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.

[0037] The contents used in this embodiment are based on mass.

[0038] The main chemical components of the magnesium-nickel-rich slag raw material used in this embodiment are analyzed by X-ray fluorescence spectroscopy, as shown in Table 1.

[0039] Table 1 Chemical composition content of magnesium-nickel-rich slag (%)

[0040]

[0041] Embodiment 1:

[0042] The invention discloses an acid-activated magnesium-nickel-rich slag geopolymer refractory cementitious material. The contents of the components are as follows: 60.00 g of magnesium-nickel-rich slag, 10.67 g of aluminum dihydrogen phosphate powder and 17.67 g of deionized water. The molar ratio of phosphorus to aluminum in the system composed of the magnesium-nickel-rich slag and aluminum dihydrogen phosphate is 0.4:1.

[0043] A method for preparing an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material comprises the following steps:

[0044] (1) Powder refinement: The magnesium-nickel-rich slag is dried in an oven at 60°C until the mass no longer changes. After cooling to room temperature, the magnesium-nickel-rich slag is ball-milled in a ball mill and then passed through a 100-mesh sieve;

[0045] (2) preparing a slurry: placing the sieved magnesium-nickel-rich slag and aluminum dihydrogen phosphate in a stirrer at 300 rpm and mechanically mixing for 2 minutes to obtain a slurry;

[0046] (3) Preparation of clean slurry: Add water to the slurry and continue mixing for 6 minutes to obtain clean slurry;

[0047] (4) Forming and curing: The clean slurry is poured into an uncovered steel mold for molding. The mold with the clean slurry is sealed and placed in a curing box for constant temperature curing at 40°C for 24 h. After demolding, the test block is placed indoors at 25°C for curing for 3 days, and then placed outdoors at 15°C for curing for 28 days to obtain a geopolymer refractory cementitious material.

[0048] According to the "Test Method for Cement Mortar Strength" (GB17671-1999), the refractory cementitious material of this embodiment was used to prepare a slurry test block, and the test block size was 40mm×40mm×160mm.

[0049] After the test block is cured indoors, it is placed in a resistance furnace for high temperature resistance test. The calcination temperatures are set at 600℃, 800℃, 1000℃ and 1200℃ respectively, and the temperature is kept for 60 minutes. The heating rate refers to the provisions of the heating curve in the "Fire Resistance Test Method for Building Components" (GB / T9978.1-2008), and the heating method is set as follows: from the starting temperature to 100℃ before the predetermined temperature, the heating rate is controlled at 10℃ / min, and the last 100℃ heating rate is controlled at 2℃ / min. After the calcined test block is naturally cooled, it is taken out and its size is measured with a vernier caliper. The compressive strength test is carried out in accordance with the "Test Method for Cement Mortar Strength" (GB17671-1999).

[0050] The refractory cementitious material of this embodiment has a 3-day compressive strength of 1.2 MPa, a 7-day compressive strength of 2.4 MPa, a 28-day compressive strength of 9.6 MPa, a compressive strength of 16.8 MPa after calcination at 1200°C, and a complete appearance.

[0051] like Figure 1 As shown, this embodiment generates more refractory favorable phases, such as magnesium phosphate, silicoaluminophosphate and Berlinite phases.

[0052] Embodiment 2:

[0053] The invention discloses an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material. The contents of the components are as follows: 60.00 g of magnesium-nickel-rich slag, 17.00 g of aluminum dihydrogen phosphate powder and 19.25 g of deionized water. The molar ratio of phosphorus to aluminum in the system composed of the magnesium-nickel-rich slag and aluminum dihydrogen phosphate is 0.6:1.

[0054] A method for preparing an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material is the same as that in Example 1.

[0055] The refractory cementitious material of this embodiment has a 3-day compressive strength of 10.4 MPa, a 7-day compressive strength of 10.0 MPa, a 28-day compressive strength of 14.4 MPa, a compressive strength of 54.4 MPa after calcination at 1200°C, and a complete appearance.

[0056] like Figure 2 As shown, in this embodiment, a dispersed diffraction peak appears at 22-27°, that is, an amorphous phase appears, indicating that a gel is generated and more refractory favorable phases are generated, such as magnesium phosphate, silicoaluminophosphate and Berlinite phases.

[0057] like Figure 6 It can be seen that in this embodiment, a flocculent gel phase is generated, which can improve the compressive strength and refractoriness.

[0058] Embodiment 3:

[0059] The invention discloses an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material. The contents of the components are as follows: 60.00 g of magnesium-nickel-rich slag, 25.21 g of aluminum dihydrogen phosphate powder and 21.30 g of deionized water. The molar ratio of phosphorus to aluminum in the system composed of the magnesium-nickel-rich slag and aluminum dihydrogen phosphate is 0.8:1.

[0060] A method for preparing an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material is the same as that in Example 1.

[0061] The refractory cementitious material of this embodiment has a 3-day compressive strength of 10.0 MPa, a 7-day compressive strength of 11.6 MPa, a 28-day compressive strength of 15.2 MPa, a compressive strength of 35.2 MPa after calcination at 1200°C, and a complete appearance.

[0062] like Figure 3 As shown, in this embodiment, a dispersed diffraction peak appears at 22-35°, that is, an amorphous phase appears, indicating that a gel is generated and more refractory favorable phases are generated, such as magnesium phosphate, silicoaluminophosphate and Berlinite phases.

[0063] Embodiment 4:

[0064] The invention discloses an acid-activated magnesium-nickel-rich slag geopolymer refractory cementitious material. The contents of the components are as follows: 60.00 g of magnesium-nickel-rich slag, 34.66 g of aluminum dihydrogen phosphate powder and 23.67 g of deionized water. The molar ratio of phosphorus to aluminum in the system composed of the magnesium-nickel-rich slag and aluminum dihydrogen phosphate is 1.0:1.

[0065] A method for preparing an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material is the same as that in Example 1.

[0066] The refractory cementitious material of this embodiment has a 3-day compressive strength of 11.8 MPa, a 7-day compressive strength of 16.0 MPa, a 28-day compressive strength of 15.6 MPa, a compressive strength of 17.6 MPa after calcination at 1200°C, and a complete appearance.

[0067] like Figure 4 As shown, in this embodiment, a dispersed diffraction peak appears at 20-32°, that is, an amorphous phase appears, indicating that a gel is generated and more refractory favorable phases are generated, such as magnesium phosphate, silicoaluminophosphate and Berlinite phases.

[0068] Embodiment 5:

[0069] The invention discloses an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material. The contents of the components are as follows: 60.00 g of magnesium-nickel-rich slag, 46.22 g of aluminum dihydrogen phosphate powder and 26.56 g of deionized water. The molar ratio of phosphorus to aluminum in the system composed of the magnesium-nickel-rich slag and aluminum dihydrogen phosphate is 1.2:1.

[0070] A method for preparing an acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material is the same as that in Example 1.

[0071] The refractory cementitious material of this embodiment has a 3-day compressive strength of 14.0 MPa, a 7-day compressive strength of 16.8 MPa, a 28-day compressive strength of 16.0 MPa, a compressive strength of 15.6 MPa after calcination at 1200°C, and a complete appearance.

[0072] like Figure 5 As shown, in this embodiment, a dispersed diffraction peak appears at 20-35°, that is, an amorphous phase appears, indicating that a gel is generated and more refractory favorable phases are generated, such as magnesium phosphate, silicoaluminophosphate and Berlinite phases.

[0073] Table 2 Case Ingredient Ratio

[0074] Case Magnesium-nickel rich slag / g Aluminum dihydrogen phosphate / g Water / g Phosphorus to aluminum molar ratio Example 1 60.0 10.67 17.67 0.4:1 Example 2 60.0 17.00 19.25 0.6:1 Example 3 60.0 25.21 21.30 0.8:1 Example 4 60.0 34.66 23.67 1.0:1 Example 5 60.0 46.22 26.56 1.2:1

[0075] Table 3 Case test results

[0076]

[0077] like Figures 1 to 5As shown, X-ray diffraction (XRD) experiments were carried out through Examples 2 to 5. Due to the appearance of dispersed diffraction peaks, i.e., amorphous phases, at room temperature, the compressive strength increased with the increase in the phosphorus-aluminum molar ratio. Example 1 did not detect particularly obvious dispersed diffraction, i.e., amorphous phases, so the strength was low at room temperature. After calcination at 1200°C, the compressive strength of the five embodiments was improved to varying degrees, and there was no collapse, peeling, etc., and the shapes were kept intact. Comparing Examples 1 and 2, it was shown that as the phosphorus-aluminum molar ratio increased from 0.4 to 0.6, the compressive strength also increased from 16.8MPa to 54.4MPa. This is mainly due to the fact that the amorphous state generated during the geological polymerization process changes to a crystalline state under the action of high temperature, thereby increasing the compressive strength. However, as the phosphorus-aluminum molar ratio of Examples 2 to 5 increased from 0.6 to 1.2, the compressive strength decreased from 54.4MPa to 15.6MPa. This is mainly due to the following two reasons: (1) Excess aluminum dihydrogen phosphate powder is not dissolved in water and exists in the gel in the form of particles. When the temperature is too high, the aluminum dihydrogen phosphate powder begins to expand, resulting in increased pores and greatly reducing the compressive strength; (2) The higher the concentration of aluminum dihydrogen phosphate solution, the more difficult it is to depolymerize the magnesium-nickel slag particles, and the lower the polymer formation rate, which has a negative impact on the compressive strength. Figure 6 As shown, by performing a scanning electron microscope (SEM) experiment on Example 2, it was found that there was a flocculent aluminum phosphate (AlPO4) phase distributed on the magnesium phosphate, which is consistent with the result of XRD detection of the amorphous phase and magnesium phosphate.

[0078] This embodiment prepares magnesium-rich nickel slag into a green refractory cementitious material at room temperature, which can not only solve the environmental problem of inefficient treatment of nickel-iron slag, but also reduce the energy problem of preparing refractory bricks with silicate cement (refractory cement) and sintered nickel-iron slag, and provides a new idea for preparing environmentally friendly refractory materials. The preparation process of this embodiment is simple, the production cost is low, and the utilization rate of solid waste is high; in addition, the refractory cementitious material prepared in this embodiment can show good compressive strength and melting point at an early stage, and after high-temperature calcination, the structure is dense due to the phase change of the organization, thereby improving the mechanical properties. Since the acid excitation reaction releases a large amount of heat, it can be used for construction in cold environments. Because it has certain strength and high-temperature stability, it can be prepared into a refractory prefabricated part.

[0079] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material, characterized in that: The refractory gelled material comprises a solid raw material and a liquid raw material, wherein the solid raw material comprises magnesium-nickel-rich slag and dihydrogen phosphate acidic activator, the molar ratio of phosphorus to aluminum of the solid raw material is (0.2-1.5):1, the liquid raw material comprises water, and the mass ratio of the liquid raw material to the solid raw material is (0.2-0.4):1; The magnesium-nickel-rich slag comprises 20-50 parts of silicon dioxide, 20-50 parts of magnesium oxide, 10-30 parts of iron oxide, 5-10 parts of aluminum oxide, 0-5 parts of calcium oxide, 0-1 parts of manganese monoxide, 0-1 parts of potassium oxide, 0-1 parts of vanadium pentoxide, 0-1 parts of nickel oxide, 0-2 parts of titanium dioxide and 0-1 parts of sulfur trioxide; The dihydrogen phosphate includes aluminum dihydrogen phosphate or magnesium dihydrogen phosphate; The method for preparing the acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material comprises the following steps: S1. preparing slurry: mechanically mixing solid raw materials, magnesium-nickel-rich slag and dihydrogen phosphate, to obtain slurry; S2, preparing a clean slurry: adding a liquid raw material to the slurry and mixing to obtain a clean slurry; S3, forming and curing: pouring the clean slurry into a mold for forming, and then curing to obtain a geopolymer refractory gelling material.

2. The acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material according to claim 1, characterized in that: In step S1, the magnesium-nickel-rich slag is powder-refined before mixing, and the specific steps are: drying the magnesium-nickel-rich slag, ball-milling the magnesium-nickel-rich slag after cooling to room temperature, and then sieving.

3. The acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material according to claim 2, characterized in that: The drying temperature is 40-80°C.

4. The acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material according to claim 2, characterized in that: The particle size of the magnesium-nickel-rich slag is 60-120 meshes.

5. The acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material according to claim 1, characterized in that: The mixing speed in steps S1 and S2 is 150-400 rpm, the mixing time in step S1 is 1-5 min, and the mixing time in step S2 is 5-10 min.

6. The acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material according to claim 1, characterized in that: The curing step in step S3 is specifically as follows: sealing the mold poured with the clean slurry, placing it in a curing box for constant temperature curing, and after demoulding, placing the test block for indoor curing, and then placing it for outdoor curing to obtain the geopolymer refractory gelling material.

7. The acid-activated magnesium-nickel-rich slag geopolymer refractory gelling material according to claim 6, characterized in that: The constant temperature curing time is 12-36 hours, the temperature is 35-50°C, the indoor curing time is 3-5 days, the temperature is 10-30°C, and the outdoor curing time is 7-28 days, the temperature is 5-20°C.

Citation Information

Patent Citations

  • Phosphoric acid excited magnesium-rich nickel slag geopolymer cementing material and preparation method thereof

    CN113880506A

  • Nickel slag cementing material for improving nickel slag activity through split-phase activation and preparation method

    CN114276097A